2010
DOI: 10.1002/jbm.a.32822
|View full text |Cite
|
Sign up to set email alerts
|

Creating conductive structures for cell growth: Growth and alignment of myogenic cell types on polythiophenes

Abstract: Conducting polymers provide suitable substrates for the in vitro study of excitable cells, including skeletal muscle cells, due to their inherent conductivity and electroactivity. The thiophene family of conducting polymers offers unique flexibility for tailoring of polymer properties as a result of the ease of functionalization of the parent monomer. This article describes the preparation of films and electrospun fibers from an ester-functionalized organic solvent-soluble polythiophene (poly-octanoic acid 2-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 49 publications
1
50
1
Order By: Relevance
“…Alignment of organic micro-or nano-fibers is beneficial for enhanced charge transport [231,232,263,264], production of polarized light emission [265,266], improved absorption and photovoltaic properties [123,267], and enhanced crystal properties [268]. Additional benefits of parallel fiber arrangement include directional cell growth [269] and guided cell differentiation [270] as well as the achievement of high-modulus, highstrength fibers, which can be used for heat-resistant and protective clothing [271,272]. The multitude of applications requiring alignment makes evident the need for straightforward and uninvolved processes for producing aligned fiber structures beyond that of templated strategies.…”
Section: Es Fabrication Of Organic Micro-and Nano-fiber Devicesmentioning
confidence: 99%
“…Alignment of organic micro-or nano-fibers is beneficial for enhanced charge transport [231,232,263,264], production of polarized light emission [265,266], improved absorption and photovoltaic properties [123,267], and enhanced crystal properties [268]. Additional benefits of parallel fiber arrangement include directional cell growth [269] and guided cell differentiation [270] as well as the achievement of high-modulus, highstrength fibers, which can be used for heat-resistant and protective clothing [271,272]. The multitude of applications requiring alignment makes evident the need for straightforward and uninvolved processes for producing aligned fiber structures beyond that of templated strategies.…”
Section: Es Fabrication Of Organic Micro-and Nano-fiber Devicesmentioning
confidence: 99%
“…In our previous investigations into the use of polythiophene substrates for the in vitro growth of skeletal muscle cells, we utilized two chemically prepared substituted polythiophenes of distinctly different surface characteristics [12]. It was demonstrated that, despite the diverse hydrophilic character of the films, both films supported the proliferation and differentiation of primary and transformed skeletal muscle myoblasts.…”
Section: Polymer Propertiesmentioning
confidence: 99%
“…A number of reports have highlighted the diversity of approaches that have been applied to improve skeletal muscle engineering, including the use of micro-patterned polymers [5][6][7], biological scaffolds [8] and synthetic polymers [9][10][11][12][13]. Synthetic scaffolds have the advantage over biologic scaffolds in that their characteristics can be defined and manipulated to be inherently pro-myogenic (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical and mechanical stimuli have demonstrated in the past to stimulate stem cells and to influence differentiation into cardiac type cells [9][10][11]. EAP coated fibres have been demonstrated to work as support for many types of cells, including neural, myogenic, and cardiac cells [12][13][14][15]. Following on from this foundation, we will produce EAP coated fibres using PPy to investigate the response from primary and stem cells.…”
Section: Introductionmentioning
confidence: 99%